The story of ink and water - Li, Qingye (Balestier Press, 2017)
A long time ago, in a beautiful little river lived Water Girl. She loved playing in the river with her river animal friends. One day, she got tired of it. A cockerel heard about this and decided to bring her to the river bank. That was when she met him. His whole body was covered in an inky black. What future does this encounter hold? [Balestier Press]
Vorabdruck mit vorläufiger Übersetzung der chinesischen Ausgabe (Zhejiang Juvenile and Children's Publishing House Co., 2013)
Keywords: Wasser; Tusche; Tuschmalerei; Papier; Pinsel; Bilderbuch